Registration of Geographic Indications of Alcohol Beverages from Abroad in Indonesia - Nurasiah, Nurasiah; Kusnafizal, Teuku; Azis, Abdul; Nur Amalina, Sharfina; Zulfan, Zulfan; Sakdiyah, Sakdiyah (Bina Nusantara University, 2022)
The research aimed to describe why alcoholic beverage products belonging to foreign countries can be registered in Indonesia's Geographical Indications (GI) protection regime. It outlined the legal implications of protecting foreign alcoholic beverage products in the GI protection regime. The research was normative legal research which was strengthened by interviews. The research shows that the protection of foreign alcoholic beverages in the national GI regime is caused by two factors, including disharmony between law 20/2016 and Permenkumham number 12 the Year 2019, and the GI regime gives each member country the freedom to apply the GI provisions in accordance with their national interests. Furthermore, the implications for the protection of foreign alcoholic beverage products in the GI protection regime in Indonesia, besides showing the inconsistency of GI protection arrangements for alcoholic beverage products, also injure the sense of justice for traditional alcoholic beverage activists who want their traditional knowledge products to be protected through the GI regime.Â